Non-aqueous electrolyte and non-aqueous electrolyte secondary battery containing that non-aqueous electrolyte

The inclusion of a specific compound and sulfur trioxide complex in the non-aqueous electrolyte enhances the cycle capacity of lithium secondary batteries by suppressing side reactions and forming a protective film on the electrode surface, addressing the insufficient cycle characteristics of existing sulfur trioxide complex-based electrolytes.

JP2024180055APending Publication Date: 2024-12-26MU IONIC SOLUTIONS CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023099481
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-16
Publication Date
2024-12-26

AI Technical Summary

Technical Problem

Existing non-aqueous electrolyte secondary batteries, such as lithium secondary batteries, do not achieve sufficient improvements in cycle characteristics despite the addition of sulfur trioxide complexes with substituent groups.

Method used

A non-aqueous electrolyte solution containing a specific compound represented by general formula (I) and a sulfur trioxide complex, with a molar ratio of 95:5 to 40:60, is used to enhance the electrolyte, which includes pyridine-sulfur trioxide, trimethylamine-sulfur trioxide, and other Lewis base compounds to suppress side reactions and improve cycle capacity.

Benefits of technology

The combination of the specific compound and sulfur trioxide complex results in a non-aqueous electrolyte with high cycle capacity, forming a protective film on the electrode surface, thereby improving the battery's cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024180055000001
    Figure 2024180055000001
  • Figure 2024180055000002
    Figure 2024180055000002
  • Figure 2024180055000003
    Figure 2024180055000003
Patent Text Reader

Abstract

To provide a non-aqueous electrolyte exhibiting high cycle capacity.SOLUTION: In a non-aqueous electrolyte, an electrolyte salt is dissolved in a non-aqueous solvent. The non-aqueous electrolyte contains a compound represented by the general formula (I) in the figure, and a sulfur trioxide complex. (In the formula, M+ represents an alkali metal cation.)SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a nonaqueous electrolyte solution and a nonaqueous electrolyte secondary battery containing the nonaqueous electrolyte solution. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries such as lithium secondary batteries are being put to practical use in a wide range of applications, from so-called consumer power sources for mobile phones, notebook computers, etc., to on-board power sources for driving automobiles, etc. However, in recent years, there has been an increasing demand for higher performance for non-aqueous electrolyte secondary batteries, and in particular, there has been a demand for improvements in various battery characteristics such as high capacity, low-temperature usage characteristics, high-temperature storage characteristics, cycle characteristics, and safety during overcharge.

[0003] To date, numerous techniques have been investigated for improving the cycle characteristics of non-aqueous electrolyte secondary batteries with respect to various battery components, including the active materials of the positive and negative electrodes and the non-aqueous electrolyte.

[0004] Patent Document 1 discloses that a non-aqueous electrolyte solution containing a sulfur trioxide complex having a substituent group improves cycle characteristics. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 2020-504434 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the electrolyte solution described in Patent Document 1 does not provide a sufficient improvement effect in terms of improving cycle characteristics.

[0007] An object of the present invention is to provide a nonaqueous electrolyte solution that exhibits high cycle capacity, and a nonaqueous electrolyte secondary battery that includes the nonaqueous electrolyte solution. [Means for solving the problem]

[0008] The present inventors have conducted detailed studies on the non-aqueous electrolytes of the above-mentioned conventional techniques, and as a result, it has been found that, although the cycle capacity of the electrolytes disclosed in Patent Document 1 is indeed improved compared to the electrolytes not containing the sulfur trioxide complex having the substituent, the improvement is not fully satisfactory. In response to this, the present inventors have found that the above problems can be solved by further adding a specific compound to the electrolyte solution, and have thus completed the present invention.

[0009] That is, the present invention is as follows. [1] A non-aqueous electrolyte solution in which an electrolyte salt is dissolved in a non-aqueous solvent, A non-aqueous electrolyte solution comprising a compound represented by the following general formula (I) and a sulfur trioxide complex:

[0010] [ka]

[0011] (In the formula, M + indicates an alkali metal cation.)

[0012] [2] The non-aqueous electrolyte solution according to [1], wherein a molar ratio of the content of the compound represented by the general formula (I):the content of the sulfur trioxide complex in the non-aqueous electrolyte solution is 95:5 to 40:60. [3] The non-aqueous electrolyte solution according to [1], wherein a molar ratio of the content of the compound represented by the general formula (I):the content of the sulfur trioxide complex in the non-aqueous electrolyte solution is 85:15 to 60:40. [4] The sulfur trioxide complex may be selected from the group consisting of pyridine-sulfur trioxide complex, trimethylamine-sulfur trioxide complex, triethylamine-sulfur trioxide complex, N,N-dimethylacetamide-sulfur trioxide complex, N,N-dimethylformamide-sulfur trioxide complex, N-methyl-2-pyrrolidone-sulfur trioxide complex, dimethylsulfone-sulfur trioxide complex, thietane 1,1-dioxide-sulfur trioxide complex, 3-sulfolene-sulfur trioxide complex, sulfolane-sulfur trioxide complex, dimethylsulfide-sulfur trioxide complex, dimethylsulfoxide-sulfur trioxide complex, 1,4-dioxane-sulfur trioxide complex, 1,3-dioxane-sulfur trioxide complex, trimethylphosphate-sulfur trioxide complex, triethylphosphate-sulfur trioxide complex, tri-n-butylphosphate-sulfur trioxide complex, triphenylphosphate-sulfur trioxide complex, tri-p-cre The nonaqueous electrolyte solution according to any one of [1] to [3], characterized in that the electrolyte is at least one selected from the group consisting of diphenyl phosphate-sulfur trioxide complex, tri-tert-butyl phosphate, trimethyl phosphite-sulfur trioxide complex, triethyl phosphite-sulfur trioxide complex, tri-n-butyl phosphite-sulfur trioxide complex, triphenyl phosphite-sulfur trioxide complex, tri-p-cresyl phosphite-sulfur trioxide complex, and tri-tert-butyl phosphite. [5] A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte in which an electrolyte salt is dissolved in a non-aqueous solvent, A non-aqueous electrolyte secondary battery, wherein the non-aqueous electrolyte is the non-aqueous electrolyte according to any one of [1] to [4]. Effect of the Invention

[0013] According to the present invention, it is possible to provide a nonaqueous electrolyte solution exhibiting high cycle capacity, and also to provide a nonaqueous electrolyte secondary battery including the nonaqueous electrolyte solution. The reason why the nonaqueous electrolyte solution having the configuration of the present invention exhibits such excellent effects is not necessarily clear, but the present inventors speculate as follows. That is, the sulfur trioxide complex is reduced on the electrode surface or reacts with the surface residues of the electrode to form a coating. At the same time, the Lewis base compound decomposed from the sulfur trioxide complex is also incorporated into the coating. It is thought that this Lewis base compound gradually reacts on the electrode surface with each cycle, and this is presumably why the cycle capacity is not improved sufficiently. On the other hand, it is believed that when the compound of the above general formula (I) is used in combination with a sulfur trioxide complex, the side reaction of the Lewis base compound is suppressed, and a nonaqueous electrolyte solution exhibiting a high cycle capacity, which is the object of the present invention, can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The following describes in detail the embodiment of the present invention. However, the following description is an example (representative example) of the embodiment of the present invention, and the present invention is not limited to these contents. In addition, the present invention can be modified and implemented as desired without departing from the gist of the present invention.

[0015] [1.Non-aqueous electrolyte] [1-1. Compounds represented by general formula (I) and sulfur trioxide complexes] A non-aqueous electrolyte solution according to an embodiment of the present invention is characterized in that an electrolyte salt is dissolved in a non-aqueous solvent, and the non-aqueous electrolyte solution contains a compound represented by the following general formula (I) and a sulfur trioxide complex.

[0016] [ka]

[0017] (In the formula, M + indicates an alkali metal cation.)

[0018] [Compound of general formula (I)]

[0019] [ka]

[0020] (In the formula, M + indicates an alkali metal cation.)

[0021] In the general formula (I), M + represents an alkali metal cation, and specific examples thereof include lithium cation, sodium cation, potassium cation, rubidium cation, and cesium cation. Among these, lithium cation, sodium cation, and potassium cation are preferred, lithium cation and sodium cation are more preferred, and lithium cation is particularly preferred.

[0022] Suitable examples of the compound represented by formula (I) include lithium fluorosulfonate, sodium fluorosulfonate, potassium fluorosulfonate, rubidium fluorosulfonate, and cesium fluorosulfonate.

[0023] Among the above compounds, lithium fluorosulfonate, sodium fluorosulfonate, and potassium fluorosulfonate are preferred, lithium fluorosulfonate and sodium fluorosulfonate are more preferred, and lithium fluorosulfonate is particularly preferred.

[0024] The content of the compound represented by the general formula (I) is not particularly limited, but is preferably 0.001% by mass to 10% by mass in 100% by mass of the nonaqueous electrolyte. Within this range, the film is sufficiently formed by reduction on the electrode surface or by reaction with the surface residue of the electrode, and there is little risk of the characteristics being deteriorated due to excessive film formation. The lower limit is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, even more preferably 0.1% by mass or more, and particularly preferably 0.6% by mass or more. The upper limit is preferably 10% by mass or less, more preferably 8% by mass or less, more preferably 5% by mass or less, particularly preferably 3% by mass or less, and most preferably 1.5% by mass or less.

[0025] [Sulfur trioxide complex] The sulfur trioxide complexes defined in this embodiment include known compounds, such as those described in Journal of Electroanalytical Chemistry and Interfacial Electrochemistry 1980, 106, 149, but are not limited thereto.

[0026] In the sulfur trioxide complex of this embodiment, the compound that forms a complex with sulfur trioxide is a compound that exhibits Lewis basicity, and examples of such compounds include nitrogen-containing compounds such as amines and amides, sulfur-containing compounds such as sulfones, sulfoxides and sulfides, and phosphorus-containing compounds such as ether compounds, phosphates and phosphites.

[0027] Specific examples of the compound that forms a complex with sulfur trioxide include amines such as pyridine, trimethylamine, triethylamine, tripropylamine, tributylamine, and N-ethyldiisopropylamine, amides such as formamide, N-methylformamide, N,N-dimethylacetamide, N,N-dimethylformamide, N,N-diethylformamide, and N-methyl-2-pyrrolidone, dimethylsulfone, ethylmethylsulfone, methylvinylsulfone, divinylsulfone, thiirane 1,1-dioxide, thietane 1,1-dioxide, 2,5-dihydrothiophene 1,1-dioxide [3-sulfolene], 2,3-dihydrothiophene 1,1-dioxide [2-sulfolene], and tetrahydrothiophene. Sulfones such as 1,1-dioxide [sulfolane], sulfides such as dimethyl sulfide, ethyl methyl sulfide, diethyl sulfide, sulfoxide compounds such as dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, ethers such as 1,4-dioxane, 1,3-dioxane, 1,3-dioxolane, dimethyl ether, ethyl methyl ether, diethyl ether, trimethyl phosphate, triethyl phosphate, tri-n-propyl phosphate, triisopropyl phosphate, tri-n-butyl phosphate, tris-2-ethylhexyl phosphate, triphenyl phosphate Preferred examples of the phosphates include tri-o-cresyl phosphate, tri-p-cresyl phosphate, tri-m-cresyl phosphate, and tri-tert-butyl phosphate; and phosphites such as trimethyl phosphite, triethyl phosphite, tri-n-propyl phosphite, triisopropyl phosphite, tri-n-butyl phosphite, tris-2-ethylhexyl phosphite, triphenyl phosphite, tri-o-cresyl phosphite, tri-p-cresyl phosphite, tri-m-cresyl phosphite, and tri-tert-butyl phosphite, but the phosphates are not limited to these.

[0028] Specific examples of the sulfur trioxide complex in the present embodiment include amine-sulfur trioxide complexes such as pyridine-sulfur trioxide complex, trimethylamine-sulfur trioxide complex, triethylamine-sulfur trioxide complex, tripropylamine-sulfur trioxide complex, tributylamine-sulfur trioxide complex, and N-ethyldiisopropylamine-sulfur trioxide complex; amide-sulfur trioxide complexes such as formamide-sulfur trioxide complex, N-methylformamide-sulfur trioxide complex, N,N-dimethylacetamide-sulfur trioxide complex, N,N-dimethylformamide-sulfur trioxide complex, N,N-diethylformamide-sulfur trioxide complex, and N-methyl-2-pyrrolidone-sulfur trioxide complex; dimethylsulfone-sulfur trioxide complex, ethylmethylsulfone-sulfur trioxide complex, methylvinylsulfone-sulfur trioxide complex, divinylsulfone-sulfur trioxide complex; thiirane 1,1-dioxide-sulfur trioxide complex; Sulfone-sulfur trioxide complexes such as 1,1-dioxide-sulfur trioxide complex, 3-sulfolene-sulfur trioxide complex, 2-sulfolene-sulfur trioxide complex, and sulfolane-sulfur trioxide complex; sulfide-sulfur trioxide complexes such as dimethyl sulfide-sulfur trioxide complex, ethyl methyl sulfide-sulfur trioxide complex, and diethyl sulfide-sulfur trioxide complex; sulfoxy-sulfur trioxide complexes such as dimethyl sulfoxide-sulfur trioxide complex, diethyl sulfoxide-sulfur trioxide complex, and tetramethylene sulfoxide-sulfur trioxide complex; 1,4-dioxane-sulfur trioxide complex, 1,3-dioxane-sulfur trioxide complex; 1,Ether-sulfur trioxide complexes such as 3-dioxolane-sulfur trioxide complex, dimethyl ether-sulfur trioxide complex, ethyl methyl ether-sulfur trioxide complex, and diethyl ether-sulfur trioxide complex; trimethyl phosphate-sulfur trioxide complex, triethyl phosphate-sulfur trioxide complex, tri-n-propyl phosphate-sulfur trioxide complex, triisopropyl phosphate-sulfur trioxide complex, tri-n-butyl phosphate-sulfur trioxide complex, tris-2-ethylhexyl phosphate-sulfur trioxide complex, triphenyl phosphate-sulfur trioxide complex, tri-o-cresyl phosphate-sulfur trioxide complex, tri-p-cresyl phosphate-sulfur trioxide complex, tri-m-cresyl phosphate-sulfur trioxide complex, and tri-te Suitable examples of the sulfur trioxide complex include phosphate-sulfur trioxide complexes such as rt-butyl phosphate-sulfur trioxide complex, trimethyl phosphite-sulfur trioxide complex, triethyl phosphite-sulfur trioxide complex, tri-n-propyl phosphite-sulfur trioxide complex, triisopropyl phosphite-sulfur trioxide complex, tri-n-butyl phosphite-sulfur trioxide complex, tris-2-ethylhexyl phosphite-sulfur trioxide complex, triphenyl phosphite-sulfur trioxide complex, tri-o-cresyl phosphite-sulfur trioxide complex, tri-p-cresyl phosphite-sulfur trioxide complex, tri-m-cresyl phosphite-sulfur trioxide complex, and tri-tert-butyl phosphite-sulfur trioxide complex. Only one of these may be used, or two or more may be used in combination.

[0029] Among the above, pyridine-sulfur trioxide complex, trimethylamine-sulfur trioxide complex, triethylamine-sulfur trioxide complex, tripropylamine-sulfur trioxide complex, formamide-sulfur trioxide complex, N-methylformamide-sulfur trioxide complex, N,N-dimethylacetamide-sulfur trioxide complex, N,N-dimethylformamide-sulfur trioxide complex, N-methyl-2-pyrrolidone-sulfur trioxide complex, dimethylsulfone-sulfur trioxide complex, ethylmethylsulfone-sulfur trioxide complex, thiirane 1,1-dioxide-sulfur trioxide complex, thietane 1,1-dioxide-sulfur trioxide complex, 3-sulfolene-sulfur trioxide complex, 2-sulfolene-sulfur trioxide complex, sulfolane-sulfur trioxide complex, dimethyl sulfide-sulfur trioxide complex, ethyl methyl sulfide-sulfur trioxide complex, dimethyl sulfoxide-sulfur trioxide complex, diethyl sulfoxide-sulfur trioxide complex, 1,4-dioxane-sulfur trioxide complex, 1,3-dioxane-sulfur trioxide complex, 1,3-dioxolane-sulfur trioxide complex, diethyl ether-sulfur trioxide complex, trimethyl phosphate-sulfur trioxide complex, triethyl phosphate-sulfur trioxide complex, tri-n-propyl phosphate-sulfur trioxide complex, tri-n-butyl phosphate-sulfur trioxide complex, tris-2-ethylhexyl phosphate-sulfur trioxide complex More preferred is one or more selected from the group consisting of triphenyl phosphate-sulfur trioxide complex, tri-o-cresyl phosphate-sulfur trioxide complex, tri-p-cresyl phosphate-sulfur trioxide complex, tri-tert-butyl phosphate-sulfur trioxide complex, trimethyl phosphite-sulfur trioxide complex, triethyl phosphite-sulfur trioxide complex, tri-n-propyl phosphite-sulfur trioxide complex, tri-n-butyl phosphite-sulfur trioxide complex, tris-2-ethylhexyl phosphite-sulfur trioxide complex, triphenyl phosphite-sulfur trioxide complex, tri-o-cresyl phosphite-sulfur trioxide complex, tri-p-cresyl phosphite-sulfur trioxide complex, and tri-tert-butyl phosphite-sulfur trioxide complex. Also, pyridine-sulfur trioxide complex, trimethylamine-sulfur trioxide complex, triethylamine-sulfur trioxide complex, tripropylamine-sulfur trioxide complex, formamide-sulfur trioxide complex, N-methylformamide-sulfur trioxide complex, N,N-dimethylacetamide-sulfur trioxide complex, N,N-dimethylformamide-sulfur trioxide complex, N-methyl-2-pyrrolidone-sulfur trioxide complex, dimethylsulfone-sulfur trioxide complex, ethylmethylsulfone-sulfur trioxide complex, thiirane 1,1-dioxide-sulfur trioxide complex, 3-sulfolene-sulfur trioxide complex, 2-sulfolene-sulfur trioxide complex, sulfolane-sulfur trioxide complex, dimethyl sulfide-sulfur trioxide complex, dimethyl sulfoxide-sulfur trioxide complex, 1,4-dioxane-sulfur trioxide complex, 1,3-dioxane-sulfur trioxide complex, 1,3-dioxolane-sulfur trioxide complex, diethyl ether-sulfur trioxide complex, trimethyl phosphate-sulfur trioxide complex, triethyl phosphate-sulfur trioxide complex, tri-n-butyl phosphate-sulfur trioxide complex, tris-2-ethylhexyl phosphate-triacid and more preferably at least one selected from the group consisting of triphenylphosphite-sulfur trioxide complex, triphenyl phosphate-sulfur trioxide complex, tri-p-cresyl phosphate-sulfur trioxide complex, tri-tert-butyl phosphate-sulfur trioxide complex, trimethyl phosphite-sulfur trioxide complex, triethyl phosphite-sulfur trioxide complex, tri-n-butyl phosphite-sulfur trioxide complex, tris-2-ethylhexyl phosphite-sulfur trioxide complex, triphenyl phosphite-sulfur trioxide complex, tri-p-cresyl phosphite-sulfur trioxide complex, and tri-tert-butyl phosphite-sulfur trioxide complex. In addition, pyridine-sulfur trioxide complex, trimethylamine-sulfur trioxide complex, triethylamine-sulfur trioxide complex, N,N-dimethylacetamide-sulfur trioxide complex, N,N-dimethylformamide-sulfur trioxide complex, N-methyl-2-pyrrolidone-sulfur trioxide complex, dimethylsulfone-sulfur trioxide complex, thietane Particularly preferred is at least one selected from 1,1-dioxide-sulfur trioxide complex, 3-sulfolene-sulfur trioxide complex, sulfolane-sulfur trioxide complex, dimethyl sulfide-sulfur trioxide complex, dimethyl sulfoxide-sulfur trioxide complex, 1,4-dioxane-sulfur trioxide complex, 1,3-dioxane-sulfur trioxide complex, trimethyl phosphate-sulfur trioxide complex, triethyl phosphate-sulfur trioxide complex, tri-n-butyl phosphate-sulfur trioxide complex, triphenyl phosphate-sulfur trioxide complex, tri-p-cresyl phosphate-sulfur trioxide complex, tri-tert-butyl phosphate-sulfur trioxide complex, trimethyl phosphite-sulfur trioxide complex, triethyl phosphite-sulfur trioxide complex, tri-n-butyl phosphite-sulfur trioxide complex, triphenyl phosphite-sulfur trioxide complex, tri-p-cresyl phosphite-sulfur trioxide complex, and tri-tert-butyl phosphite-sulfur trioxide complex.

[0030] The content of the sulfur trioxide complex in this embodiment is not particularly limited, but is preferably 0.001% by mass to 5% by mass in 100% by mass of the nonaqueous electrolyte. This is because within this range, the formation of the coating is sufficient, and there is little risk of the characteristics being deteriorated due to the excessive formation of the coating. The lower limit is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, even more preferably 0.1% by mass or more, and particularly preferably 0.2% by mass or more. The upper limit is preferably 5% by mass or less, more preferably 3% by mass or less, more preferably 1.5% by mass or less, particularly preferably 0.9% by mass or less, and most preferably 0.5% by mass or less.

[0031] Furthermore, the molar ratio of the content of the compound represented by general formula (I) to the sulfur trioxide complex in the nonaqueous electrolyte is preferably 98:2 to 30:70 because side reactions of the sulfur trioxide complex on the electrode surface are less likely to proceed, more preferably 95:5 to 40:60, and particularly preferably 85:15 to 60:40. This range is considered to be a molar ratio that not only can suppress side reactions of the sulfur trioxide complex, but also allows a good quality coating to be formed by the electrophilicity of the Lewis base compound decomposed from the sulfur trioxide complex and the general formula (I). When two or more kinds of the compound represented by the general formula (I) and the sulfur trioxide complex are contained, the molar ratio of the total content thereof is preferably within the above range.

[0032] [1-2. Electrolytes] <Lithium salt> As the electrolyte in the non-aqueous electrolyte solution according to the present embodiment, a lithium salt is usually used. The lithium salt is not particularly limited as long as it is known to be used for this purpose, and any lithium salt can be used, and specifically, the following can be mentioned. Examples include lithium fluoroborate, lithium fluorophosphate, lithium tungstate, lithium carboxylate, lithium sulfonate, lithium imide, lithium methide, lithium oxalate, and fluorine-containing organic lithium salts. Among them, the lithium fluoroborate salt is LiBF4; the lithium fluorophosphate salt is LiPF6, Li2PO3F, LiPO2F2; the lithium sulfonate salt is CH3SO3Li; the lithium imide salt is LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, lithium cyclic 1,2-perfluoroethane disulfonylimide, lithium cyclic 1,3-perfluoropropane disulfonylimide; the lithium methide salt is LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, and LiN(CF3SO2)2. iC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3; as lithium oxalate salts, lithium difluorooxalatoborate, lithium bis(oxalato)borate, lithium tetrafluorooxalatophosphite, lithium difluorobis(oxalato)phosphite, lithium tris(oxalato)phosphite, etc. are more preferred because they have the effect of improving low-temperature output characteristics, high-rate charge / discharge characteristics, impedance characteristics, high-temperature storage characteristics, cycle characteristics, etc. More preferred are LiPF6, LiN(FSO2)2 and lithium bis(oxalato)borate, and particularly preferred is LiPF6. The above electrolyte salts may be used alone or in combination of two or more kinds.

[0033] The combination of two or more kinds of lithium salts as electrolytes is not particularly limited, but includes LiPF6 and LiN(FSO2)2; LiPF6 and LiBF4; LiPF6 and LiN(CF3SO2)2; LiBF4 and LiN(FSO2)2; LiBF4 and LiPF6 and LiN(FSO2)2. Among them, LiPF6 and LiN(FSO2)2; LiPF6 and LiBF4; LiBF4, LiPF6 and LiN(FSO2)2 are preferred.

[0034] The content of the electrolyte in the non-aqueous electrolyte solution (the total content when two or more kinds are used) is not particularly limited, but is preferably 8 to 18% by mass based on the total amount of the non-aqueous electrolyte solution. That is, the content is usually 8% by mass or more, preferably 8.5% by mass or more, more preferably 9% by mass or more, and is usually 18% by mass or less, preferably 17% by mass or less, more preferably 16% by mass or less. When the content of the electrolyte is within the above range, the electrical conductivity becomes appropriate for the battery operation, and therefore sufficient output characteristics tend to be obtained.

[0035] [1-3. Nonaqueous solvents] The non-aqueous electrolyte according to one embodiment of the present invention, like a general non-aqueous electrolyte, usually contains a non-aqueous solvent that dissolves the above-mentioned electrolyte as its main component. The non-aqueous solvent used is not particularly limited as long as it dissolves the above-mentioned electrolyte, and a known organic solvent can be used. Examples of the organic solvent include, but are not limited to, saturated cyclic carbonates, chain carbonates, chain carboxylates, cyclic carboxylates, etc. The organic solvents can be used alone or in combination of two or more.

[0036] The combination of two or more organic solvents is not particularly limited, and examples thereof include saturated cyclic carbonates and chain carbonates, saturated cyclic carbonates and chain carboxylates, cyclic carboxylates or chain carbonates, and saturated cyclic carbonates, chain carbonates and chain carboxylates. Among these, saturated cyclic carbonates and chain carbonates, and saturated cyclic carbonates, chain carbonates and chain carboxylates are preferred.

[0037] [1-3-1. Saturated cyclic carbonates] Examples of saturated cyclic carbonates include those having an alkylene group having 2 to 4 carbon atoms, and saturated cyclic carbonates having 2 to 3 carbon atoms are preferably used from the viewpoint of improving battery characteristics resulting from an improvement in the degree of dissociation of lithium ions. Specific examples of the saturated cyclic carbonate include ethylene carbonate, propylene carbonate, butylene carbonate, etc. Among them, ethylene carbonate or propylene carbonate is preferred, and ethylene carbonate, which is less susceptible to oxidation and reduction, is more preferred. The saturated cyclic carbonate may be used alone or in any combination and ratio of two or more.

[0038] The content of the saturated cyclic carbonate is not particularly limited, and may be any content as long as it does not significantly impair the effects of the present invention according to this embodiment, but is preferably 3 to 90% by volume based on the total amount of the nonaqueous solvent in the nonaqueous electrolyte. Here, the content is usually 3% by volume or more, preferably 5% by volume or more, and is usually 90% by volume or less, preferably 85% by volume or less, and more preferably 80% by volume or less. By setting the content of the saturated cyclic carbonate within this range, the decrease in electrical conductivity due to the decrease in the dielectric constant of the nonaqueous electrolyte is avoided, and the large current discharge characteristics and cycle characteristics of the nonaqueous electrolyte secondary battery are easily in a good range, and the oxidation and reduction resistance of the nonaqueous electrolyte is improved, and the stability to the negative electrode and the stability during high-temperature storage tend to be improved. In the present embodiment, the volume % refers to the volume at 25° C. and 1 atmospheric pressure.

[0039] [1-3-2. Chain carbonate] As the chain carbonate, for example, one having 3 to 7 carbon atoms is used, and in order to adjust the viscosity of the electrolyte solution within an appropriate range, a chain carbonate having 3 to 5 carbon atoms is preferably used. Specific examples of the chain carbonate include dimethyl carbonate, diethyl carbonate, di-n-propyl carbonate, diisopropyl carbonate, n-propyl isopropyl carbonate, ethyl methyl carbonate, and methyl-n-propyl carbonate. Dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate are particularly preferred.

[0040] The content of the chain carbonate is not particularly limited, but is preferably 15 to 90% by volume relative to the total amount of the nonaqueous solvent in the nonaqueous electrolyte. Here, the content is usually 15% by volume or more, preferably 20% by volume or more, more preferably 25% by volume or more, and is usually 90% by volume or less, preferably 85% by volume or less, more preferably 80% by volume or less. By setting the content of the chain carbonate within the above range, the viscosity of the nonaqueous electrolyte can be set in an appropriate range, the decrease in ion conductivity can be suppressed, and the output characteristics of the nonaqueous electrolyte secondary battery can be easily set in a good range.

[0041] Furthermore, by combining a specific chain carbonate with ethylene carbonate in a specific content, the battery performance can be significantly improved. For example, when dimethyl carbonate and ethyl methyl carbonate are selected as the specific chain carbonate, the content of ethylene carbonate is not particularly limited and is arbitrary as long as it does not significantly impair the effects of the present invention according to this embodiment, but is preferably 15 to 45% by volume based on the total amount of the non-aqueous solvent in the non-aqueous electrolyte solution. Here, the content is usually 15% by volume or more, preferably 20% by volume or more, and usually 45% by volume or less, preferably 40% by volume or less. The content of dimethyl carbonate is preferably 20 to 50% by volume based on the total amount of the nonaqueous solvent in the nonaqueous electrolyte solution, and the content is usually 20% by volume or more, preferably 30% by volume or more, and usually 50% by volume or less, preferably 45% by volume or less. The content of ethyl methyl carbonate is preferably 20 to 50% by volume based on the total amount of the non-aqueous solvent in the non-aqueous electrolyte. The content is usually 20% by volume or more, preferably 30% by volume or more, and usually 50% by volume or less, preferably 45% by volume or less. By setting the content within the above range, the high temperature stability is excellent and gas generation tends to be suppressed.

[0042] [1-3-3. Fluorinated chain carbonates] In addition, chain carbonates having fluorine atoms (hereinafter, sometimes abbreviated as "fluorinated chain carbonate") can also be suitably used. The number of fluorine atoms in the fluorinated chain carbonate is not particularly limited, but is preferably 1 to 8. Here, the number of fluorine atoms is usually 8 or less, preferably 6 or less, and more preferably 4 or less. The lower limit is usually 1 or more, preferably 2 or more, and more preferably 3 or more. When the fluorinated chain carbonate has multiple fluorine atoms, the multiple fluorine atoms may be bonded to the same carbon or different carbons.

[0043] Suitable examples of the fluorinated chain carbonate include fluorinated dimethyl carbonate derivatives such as fluoromethyl methyl carbonate and bisfluoromethyl carbonate; fluorinated ethyl methyl carbonate derivatives such as 2-fluoroethyl methyl carbonate, ethyl-2-fluoromethyl carbonate, 2,2-difluoroethyl methyl carbonate and 2,2,2-trifluoroethyl methyl carbonate; fluorinated diethyl carbonate derivatives such as ethyl-2-fluoroethyl carbonate and bis(2,2,2-trifluoroethyl)carbonate; fluorinated methylpropyl carbonate derivatives such as 2,2,3,3-tetrafluoropropyl methyl carbonate, and dipropyl carbonate derivatives such as bis(2,2,3,3-tetrafluoropropyl)carbonate and bis(1,1,1,3,3,3-hexafluoropropan-2-yl)carbonate. The fluorinated chain carbonates may be used alone or in any combination of two or more kinds in any ratio.

[0044] In addition, it is more preferable to use a fluorinated chain carbonate together with a saturated cyclic carbonate and a chain carbonate, since the effect of the present invention is significantly enhanced. In this case, the content of the fluorinated chain carbonate relative to the total amount of the nonaqueous solvent in the nonaqueous electrolyte is preferably 1% by volume to 40% by volume. Here, the lower limit of the content is preferably 1% by volume, more preferably 5% by volume, and even more preferably 7% by volume. The upper limit of the content is preferably 40% by volume, more preferably 30% by volume, even more preferably 20% by volume, and particularly preferably 15% by volume.

[0045] [1-3-3. Chain carboxylate esters] Examples of the chain carboxylate include methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, methyl valerate, methyl isobutyrate, ethyl isobutyrate, and methyl pivalate. Among them, methyl acetate, ethyl acetate, propyl acetate, or butyl acetate is preferred from the viewpoint of improving battery characteristics. Chain carboxylates in which part of the hydrogen of the above-mentioned complex is replaced with fluorine (e.g., methyl trifluoroacetate, ethyl trifluoroacetate, etc.) can also be suitably used. These may be used alone or in combination of two or more.

[0046] The content of the chain carboxylate is preferably 1 to 70% by volume based on the total amount of the nonaqueous solvent in the nonaqueous electrolyte. Here, the content is usually 1% by volume or more, preferably 5% by volume or more, and more preferably 15% by volume or more. Within this range, the electrical conductivity of the nonaqueous electrolyte is improved, and the large-current discharge characteristics of the nonaqueous electrolyte secondary battery are easily improved. In addition, the content of the chain carboxylate is usually 70% by volume or less, preferably 50% by volume or less, and more preferably 40% by volume or less. By setting the upper limit in this way, the viscosity of the nonaqueous electrolyte is in an appropriate range, a decrease in electrical conductivity is avoided, an increase in the negative electrode resistance is suppressed, and the large-current discharge characteristics of the nonaqueous electrolyte secondary battery are easily in a good range.

[0047] [1-3-4. Cyclic carboxylate esters] Examples of the cyclic carboxylate include γ-butyrolactone and γ-valerolactone. Among these, γ-butyrolactone is more preferable. Cyclic carboxylates in which some of the hydrogen atoms of the above-mentioned complexes are replaced with fluorine can also be used. These may be used alone or in combination of two or more.

[0048] The content of the cyclic carboxylate is preferably 1 to 70% by volume based on the total amount of the nonaqueous solvent in the nonaqueous electrolyte. Here, the content is usually 1% by volume or more, preferably 5% by volume or more, and more preferably 15% by volume or more. Within this range, the electrical conductivity of the nonaqueous electrolyte is improved, and the large-current discharge characteristics of the nonaqueous electrolyte secondary battery are easily improved. In addition, the content of the cyclic carboxylate is usually 70% by volume or less, preferably 50% by volume or less, and more preferably 40% by volume or less. By setting the upper limit in this way, the viscosity of the nonaqueous electrolyte is in an appropriate range, a decrease in electrical conductivity is avoided, an increase in the negative electrode resistance is suppressed, and the large-current discharge characteristics of the nonaqueous electrolyte secondary battery are easily in a good range.

[0049] [1-4. Auxiliaries] The non-aqueous electrolyte according to the present embodiment may contain various auxiliary agents within a range that does not significantly impair the effects of the present invention. As the auxiliary agent, any conventionally known one may be used. In addition, the auxiliary agent may be used alone, or two or more kinds may be used in any combination and ratio.

[0050] Examples of the auxiliary agent that may be contained in the non-aqueous electrolyte include cyclic carbonates having carbon-carbon unsaturated bonds, fluorine-containing cyclic carbonates, compounds having an isocyanate group, organic compounds having an isocyanuric acid skeleton, sulfur-containing organic compounds, phosphorus-containing organic compounds, organic compounds having a cyano group, silicon-containing compounds, aromatic compounds, non-fluorine-containing carboxylic acid esters, cyclic compounds having an ether bond, carboxylic acid anhydrides, borate anion-containing compounds, phosphate anion-containing compounds having P=O bonds and PF bonds, anion-containing compounds having S=O bonds, and oxalate complex anion-containing compounds. For example, compounds described in International Publication No. 2015 / 111676 can be mentioned.

[0051] Among these, at least one anion-containing compound selected from a phosphate anion-containing compound having a PF bond and a P=O bond, an anion-containing compound having an S=O bond, and an oxalate complex anion-containing compound (hereinafter also referred to as a "specific anion-containing compound"), and / or at least one carbonate compound selected from a cyclic carbonate having a carbon-carbon unsaturated bond and a fluorine-containing cyclic carbonate (hereinafter also referred to as a "specific carbonate compound") is preferred.

[0052] The content of the auxiliary is not particularly limited and may be any amount as long as it does not significantly impair the effects of the present invention, but is preferably 0.001 to 10% by mass based on the total amount of the nonaqueous electrolyte solution. Here, the content is usually 0.001% by mass or more, preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and is usually 10% by mass or less, preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 1% by mass or less, and particularly preferably less than 1% by mass.

[0053] The cyclic compound having an ether bond can be used as an auxiliary in the non-aqueous electrolyte, and also includes those that can be used as a non-aqueous solvent as described in [1-3. Non-aqueous solvent]. When the cyclic compound having an ether bond is used as an auxiliary, it is preferably used in an amount of less than 4 mass%. The borate anion-containing compound, the oxalate complex anion-containing compound, the monofluorophosphate anion-containing compound, and the difluorophosphate anion-containing compound can be used as an auxiliary in the nonaqueous electrolyte, and also include those that can be used as electrolytes as described in "1-2. Electrolyte". When these compounds are used as auxiliary agents, they are preferably used in an amount of less than 3 mass%.

[0054] [1-4-1. Specific anion-containing compounds] The specific anion-containing compound is usually an acid or a salt, and is preferably a salt, and the counter cation is preferably an alkali metal cation such as lithium, sodium, or potassium, and more preferably a lithium cation. At least one anion-containing compound selected from a phosphate anion-containing compound having a PF bond and a P=O bond, an anion-containing compound having an S=O bond, and an oxalate complex anion-containing compound can be used alone or in combination of two or more in any ratio. Among these, from the viewpoint of suppressing the amount of gas generated after high-temperature storage, a phosphate anion-containing compound having a PF bond and a P=O bond is preferred.

[0055] [1-4-1-1. Phosphate anion-containing compounds having PF bonds and P=O bonds] Examples of phosphate anion-containing compounds having FP bonds and P=O bonds include PO3F 2- Monofluorophosphate anion, such as PO2F2 - and the like. Among these, compounds containing difluorophosphate anions are preferred from the viewpoint of the balance between the output characteristics of the battery and the protection of the electrode interface.

[0056] [1-4-1-2. Anion-containing compounds with S=O bonds] An example of an anion-containing compound having an S=O bond is (FSO2)2N - , (FSO2)(CF3SO2)N- Fluorosulfonylimide anions such as (FSO2)3C - Compounds containing fluorosulfonylmethide anion such as CH3SO4 - Examples of the compound include compounds containing alkyl sulfate anions such as those mentioned above. Among these, compounds containing a fluorosulfonylimide anion are preferred from the viewpoint of the balance between the output characteristics of the battery and the protection of the electrode interface.

[0057] [1-4-1-3. Compounds containing oxalate complex anions] The oxalate complex anion-containing compound is not particularly limited as long as it contains an anion having an oxalate complex in the molecule.The oxalate complex anion-containing compound is a compound containing an anion of an acid that forms a complex by coordinating or bonding with oxalic acid to a central atom, and can be exemplified by a compound containing a boron oxalate complex anion in which oxalic acid is coordinated or bonded to a boron atom, and a phosphorus oxalate complex anion in which oxalic acid is coordinated or bonded to a phosphorus atom. Examples of the boron oxalate complex anion include a bis(oxalate)borate anion and a difluorooxalateborate anion. Examples of the phosphorus oxalate complex anion include a tetrafluorooxalate phosphate anion, a difluorobis(oxalate)phosphate anion and a tris(oxalate)phosphate anion. Among these, from the viewpoint of forming a stable composite coating on the surface of the electrode, a compound containing a boron oxalate complex anion is preferred, and a compound containing a bis(oxalate)borate anion is more preferred.

[0058] (Content of specific anion-containing compounds) When the non-aqueous electrolyte contains a specific anion-containing compound, the content of the specific anion-containing compound (the total content when two or more kinds are contained) in the total amount of the non-aqueous electrolyte is preferably 0.001 to 5 mass %. Here, the content is preferably 0.001 mass % or more, more preferably 0.01 mass % or more, even more preferably 0.1 mass % or more, and is preferably 5 mass % or less, more preferably 4 mass % or less, even more preferably 3 mass % or less. If the content of the specific anion-containing compound is within the above range, the battery characteristics, particularly the direct current resistance (DCR) retention rate after high-temperature storage, can be significantly improved, and the amount of gas generated after high-temperature storage can be significantly suppressed. Although the reason for this is unclear, it is believed that the content of the specific anion-containing compound within the above mass ratio range can minimize side reactions of the components of the nonaqueous electrolyte on the electrode surface. The identification and content of specific anion-containing compounds is determined by nuclear magnetic resonance (NMR) spectroscopy.

[0059] (Mass ratio of specific anion-containing compound to compound represented by general formula (I)) The mass ratio of the content of the specific anion-containing compound (the total amount of the specific anion-containing compound when two or more types are used) to the content of the compound represented by general formula (I) (specific anion-containing compound [g] / compound represented by general formula (I) [g]) is preferably 0.01 to 100. Here, the mass ratio is usually 0.01 or more, preferably 0.05 or more, more preferably 0.3 or more, and is usually 100 or less, preferably 10 or less, more preferably 5 or less, and even more preferably 4 or less. When the mass ratio is within the above range, the battery characteristics, particularly the DCR retention rate after high-temperature storage, can be significantly improved, and the amount of gas generated after high-temperature storage can be significantly suppressed. Although the reason for this is unclear, it is believed that by containing the compound represented by general formula (I) and the specific anion-containing compound within the above mass ratio range, the side reaction of the components of the non-aqueous electrolyte on the electrode surface can be minimized.

[0060] (Mass ratio of specific anion-containing compound to electrolyte) When the non-aqueous electrolyte contains a specific anion-containing compound, the mass ratio of the content of the specific anion-containing compound (the total amount of the specific anion-containing compound when two or more types are used) to the content of the electrolyte (specific anion-containing compound [g] / electrolyte [g]) is preferably 0.00005 to 0.5. Here, the mass ratio is usually 0.00005 or more, preferably 0.001 or more, more preferably 0.01 or more, even more preferably 0.02 or more, even more preferably 0.025 or more, and usually 0.5 or less, preferably 0.45 or less, more preferably 0.4 or less, even more preferably 0.35 or less. When the mass ratio is within the above range, the battery characteristics, particularly the DCR retention rate after high-temperature storage, can be significantly improved, and the amount of gas generated after high-temperature storage can be significantly suppressed. Although the reason for this is unclear, it is believed that by containing a specific anion-containing compound and an electrolyte within the above mass ratio range, the side reaction of the electrolyte in the battery system can be minimized.

[0061] [1-4-2. Specific carbonate compounds] The non-aqueous electrolyte preferably contains at least one carbonate compound selected from the group consisting of cyclic carbonates having a carbon-carbon unsaturated bond and cyclic carbonates having a fluorine atom. Among these, it is preferable to contain a cyclic carbonate having a carbon-carbon unsaturated bond, and it is more preferable to contain vinylene carbonate. These may be used alone or in combination of two or more in any ratio. It is preferable to combine an unsaturated cyclic carbonate with a fluorinated cyclic carbonate, more preferably a combination of vinylene carbonate with a fluorinated cyclic carbonate or a combination of an unsaturated cyclic carbonate with monofluoroethylene carbonate, and even more preferably a combination of vinylene carbonate with monofluoroethylene carbonate.

[0062] (Content of specific carbonate compounds) The content of the specific carbonate compound in the total amount of the nonaqueous electrolyte solution (the total amount when two or more kinds are used) is preferably 0.001 to 10 mass %, where the content is usually 0.001 mass % or more, preferably 0.01 mass % or more, more preferably 0.1 mass % or more, and even more preferably 0.5 mass % or more, and is usually 10 mass % or less, preferably 5 mass % or less, more preferably 4 mass % or less, and even more preferably 3 mass % or less. If the content of the specific carbonate compound is within the above range, the battery characteristics, particularly the durability, can be improved. Although the reason for this is unclear, it is believed that the inclusion of the carbonate compound at this ratio forms a coating on the electrode, minimizing the side reaction of the components of the non-aqueous electrolyte. The identification and content of specific carbonate compounds is determined by nuclear magnetic resonance (NMR) spectroscopy.

[0063] (Mass ratio of specific carbonate compound to compound represented by general formula (I)) The mass ratio of the content of the specific carbonate compound (the total amount when two or more kinds are used) to the content of the compound represented by the general formula (I) (specific carbonate compound [g] / compound represented by the general formula (I) [g]) is preferably 0.01 to 100. Here, the mass ratio is usually 0.01 or more, preferably 0.05 or more, more preferably 0.3 or more, and even more preferably 0.5 or more, and is usually 100 or less, preferably 10 or less, more preferably 5 or less, and even more preferably 4 or less. If the mass ratio is within the above range, the battery characteristics, especially the durability, can be improved. The reason for this is unclear, but it is thought that by containing the specific carbonate compound within the above range of mass ratio, a coating is formed on the electrode, and the side reaction of the components of the non-aqueous electrolyte can be minimized.

[0064] (mass ratio of specific carbonate compound to electrolyte) In the non-aqueous electrolyte, the mass ratio of the content of the specific carbonate compound (the total amount of the specific carbonate compound when two or more kinds are used) to the content of the electrolyte (specific carbonate compound [g] / electrolyte [g]) is preferably 0.00005 to 0.5. Here, the mass ratio is usually 0.00005 or more, preferably 0.001 or more, more preferably 0.01 or more, even more preferably 0.02 or more, even more preferably 0.025 or more, and is usually 0.5 or less, preferably 0.45 or less, more preferably 0.4 or less, even more preferably 0.35 or less. If the mass ratio is within the above range, the battery characteristics, especially the durability, can be improved. The reason for this is unclear, but it is thought that by containing the carbonate compound and the electrolyte within the above range of the mass ratio, a coating is formed on the electrode, and the side reaction of the electrolyte in the battery system is minimized.

[0065] [1-4-2-1. Cyclic carbonates having carbon-carbon unsaturated bonds] The cyclic carbonate having a carbon-carbon unsaturated bond (hereinafter also referred to as "unsaturated cyclic carbonate") is not particularly limited as long as it is a cyclic carbonate having a carbon-carbon double bond or a carbon-carbon triple bond. Cyclic carbonates having an aromatic ring are also included in the unsaturated cyclic carbonate. Examples of the unsaturated cyclic carbonate include vinylene carbonates, ethylene carbonates substituted with a substituent having an aromatic ring, a carbon-carbon double bond or a carbon-carbon triple bond, phenyl carbonates, vinyl carbonates, allyl carbonates, catechol carbonates, etc. Among these, vinylene carbonates and ethylene carbonates substituted with a substituent having an aromatic ring, a carbon-carbon double bond or a carbon-carbon triple bond are preferred.

[0066] Examples of vinylene carbonates include vinylene carbonate, methylvinylene carbonate, 4,5-dimethylvinylene carbonate, phenylvinylene carbonate, 4,5-diphenylvinylene carbonate, vinylvinylene carbonate, 4,5-vinylvinylene carbonate, allylvinylene carbonate, and 4,5-diallylvinylene carbonate. Examples of ethylene carbonates substituted with a substituent having an aromatic ring or a carbon-carbon double bond or a carbon-carbon triple bond include vinyl ethylene carbonate, 4,5-divinyl ethylene carbonate, 4-methyl-5-vinyl ethylene carbonate, 4-allyl-5-vinyl ethylene carbonate, ethynyl ethylene carbonate, 4,5-diethynyl ethylene carbonate, 4-methyl-5-ethynyl ethylene carbonate, 4-vinyl-5-ethynyl ethylene carbonate, 4-allyl-5-ethynyl ethylene carbonate, phenyl ethylene carbonate, 4,5-diphenyl ethylene carbonate, 4-phenyl-5-vinyl ethylene carbonate, 4-allyl-5-phenyl ethylene carbonate, allyl ethylene carbonate, 4,5-diallyl ethylene carbonate, and 4-methyl-5-allyl ethylene carbonate. Among these, vinylene carbonate, vinyl ethylene carbonate, and ethynyl ethylene carbonate are preferred since they form a more stable composite coating on the electrode, and one or more selected from vinylene carbonate and vinyl ethylene carbonate are more preferred, with vinylene carbonate being even more preferred. The unsaturated cyclic carbonates can be used alone or in combination of two or more kinds in any ratio.

[0067] [1-4-2-2. Cyclic carbonates containing fluorine atoms] The fluorine atom-containing cyclic carbonate is not particularly limited as long as it has a cyclic carbonate structure and contains a fluorine atom. Examples of cyclic carbonates having fluorine atoms include fluorinated cyclic carbonates having an alkylene group with 2 to 6 carbon atoms, and derivatives thereof, such as fluorinated ethylene carbonate (fluoroethylene carbonate) and derivatives thereof, and ethylene carbonate having a fluorine-containing group. Examples of derivatives of fluorinated ethylene carbonate include fluorinated ethylene carbonate substituted with an alkyl group (e.g., an alkyl group with 1 to 4 carbon atoms). Among these, fluoroethylene carbonate having 1 to 8 fluorine atoms and derivatives thereof are preferred.

[0068] Examples of fluoroethylene carbonate and derivatives thereof having 1 to 8 fluorine atoms, as well as ethylene carbonate having a fluorine-containing group, include monofluoroethylene carbonate, 4,4-difluoroethylene carbonate, 4,5-difluoroethylene carbonate, 4-fluoro-4-methylethylene carbonate, 4,5-difluoro-4-methylethylene carbonate, 4-fluoro-5-methylethylene carbonate, 4,4-difluoro-5-methylethylene carbonate, 4-(fluoromethyl)-ethylene carbonate, 4-(difluoromethyl)-ethylene carbonate, 4-(trifluoromethyl)-ethylene carbonate, 4-(fluoromethyl)-4-fluoroethylene carbonate, 4-(fluoromethyl)-5-fluoroethylene carbonate, 4-fluoro-4,5-dimethylethylene carbonate, 4,5-difluoro-4,5-dimethylethylene carbonate, and 4,4-difluoro-5,5-dimethylethylene carbonate. Among these, from the viewpoints of imparting high ionic conductivity to the electrolyte and facilitating the formation of a stable interface protective film, one or more selected from monofluoroethylene carbonate, 4,4-difluoroethylene carbonate, and 4,5-difluoroethylene carbonate are preferred. The fluorine atom-containing cyclic carbonates can be used alone or in combination of two or more kinds in any ratio.

[0069] [2. Non-aqueous electrolyte secondary battery] A nonaqueous electrolyte secondary battery according to one embodiment of the present invention is a nonaqueous electrolyte secondary battery comprising a positive electrode having a positive electrode active material capable of absorbing and releasing metal ions, and a negative electrode having a negative electrode active material capable of absorbing and releasing metal ions, and comprising a nonaqueous electrolyte.

[0070] [2-1. Non-aqueous electrolyte] As the non-aqueous electrolyte solution, the above-mentioned non-aqueous electrolyte solution is used. Note that, within the scope of the present invention, it is also possible to mix the above-mentioned non-aqueous electrolyte solution with other non-aqueous electrolyte solutions.

[0071] [2-2. Positive electrode] The positive electrode has a positive electrode active material on at least a portion of the surface of a current collector.

[0072] [2-2-1. Positive electrode active material] The positive electrode active material (lithium transition metal compound) used in the positive electrode will be described below.

[0073] [2-2-1-1. Lithium transition metal compounds] The lithium transition metal compound is a compound having a structure capable of desorbing and inserting lithium ions, and examples thereof include sulfides, phosphate compounds, silicate compounds, borate compounds, lithium transition metal composite oxides, etc. Among these, phosphate compounds and lithium transition metal composite oxides are preferred, and lithium transition metal composite oxides are more preferred. Examples of lithium transition metal composite oxides include those having a spinel structure that allows three-dimensional diffusion, and those having a layered structure that allows two-dimensional diffusion of lithium ions.

[0074] Those having a spinel structure are generally represented by the following composition formula (1). Li x’ M'2O4···(1) (In formula (1), x' is 1≦x'≦1.5, and M' represents at least one transition metal element.) Specifically, LiMn2O4, LiCoMnO4, LiNi 0.5 Mn1.5 O4, LiCoVO4, etc.

[0075] Those having a layered structure are generally represented by the following composition formula (2). Li 1+x M'O2···(2) (In formula (2), x is −0.1≦x≦0.5, and M′ represents at least one transition metal element.) Specifically, LiCoO2, LiNiO2, LiNi 0.85 Co 0.10 Al 0.05 O2, LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 0.33 Co 0.33 Mn 0.33 O2, Li 1.05 Ni 0.33 Co 0.33 Mn 0.33 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, Li 1.05 Ni 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 Examples include O2.

[0076] Among these, from the viewpoint of improving the battery capacity, a lithium transition metal composite oxide having a layered structure is preferred, and a transition metal composite oxide represented by the following composition formula (3) is more preferred. Li a1 Ni b1 M” c1 O2···(3) (In formula (3), a1, b1, and c1 are numerical values ​​that satisfy 0.90≦a1≦1.10, 0.30≦b1≦0.99, and 0.01≦c1≦0.5, respectively, and satisfy 0.50≦b1+c1 and b1+c1=1. M″ represents at least one element selected from the group consisting of Mn, Al, Mg, Zr, Fe, Ti, and Er.)

[0077] In particular, from the viewpoint of the structural stability of the lithium transition metal composite oxide, the lithium transition metal compound is preferably a transition metal oxide represented by the following composition formula (4). Li a2 Ni b2 Co c2 M” d2 O2···(4) (In formula (4), a2, b2, and c2 are numerical values ​​that satisfy 0.90≦a2≦1.10, 0.50≦b2≦0.99, and 0.01≦c2<0.50, respectively, and b2+c2=1 is satisfied. M″ represents at least one element selected from the group consisting of Mn, Al, Mg, Zr, Fe, Ti, and Er.)

[0078] A specific example of the lithium transition metal oxide represented by the composition formula (4) is LiNi 0.85 Co 0.10 Al 0.05 O2, LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, Li 1.05 Ni 0.50 Co 0.20 Mn 0.30 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, etc.

[0079] In each composition formula, M' and M" each preferably contain Mn or Al, more preferably contain Mn, and further preferably are Mn or Al. This is because the structural stability of the lithium transition metal oxide is enhanced and structural deterioration during repeated charge and discharge is suppressed.

[0080] [2-2-1-2. Introduction of different elements] Furthermore, the lithium transition metal composite oxide may contain elements (foreign elements) other than the elements contained in the above composition formulas (1) to (4).

[0081] [2-2-1-3. Surface coating] The positive electrode active material may have a surface-attached substance having a different composition from the positive electrode active material. Examples of the surface-attached substance include oxides such as aluminum oxide, sulfates such as lithium sulfate, and carbonates such as lithium carbonate. These surface-adhering substances can be attached to the surface of the positive electrode active material, for example, by dissolving or suspending them in a solvent, adding them to the positive electrode active material by impregnation, and drying them.

[0082] The amount of the surface-attaching substance is preferably 1 μmol / g or more, more preferably 10 μmol / g or more, and is usually 1 mmol / g or less, relative to the positive electrode active material. In this specification, a positive electrode active material having the above-mentioned surface-adhering substance attached to its surface is also referred to as a "positive electrode active material".

[0083] [2-2-1-4. Blend] These positive electrode active materials may be used alone or in any combination of two or more in any ratio.

[0084] [2-2-2. Positive electrode composition and manufacturing method] The configuration and manufacturing method of the positive electrode will be described below. In this embodiment, the positive electrode using the positive electrode active material can be manufactured by a conventional method. That is, the positive electrode active material and the binder, and if necessary, the conductive material and the thickener, etc. are mixed in a dry state to form a sheet, which is then pressed onto the positive electrode current collector, or these materials are dissolved or dispersed in a liquid medium such as an aqueous solvent or an organic solvent to form a slurry, which is then applied to the positive electrode current collector and dried to form a positive electrode active material layer on the current collector, thereby obtaining a positive electrode. In addition, for example, the above-mentioned positive electrode active material may be roll-formed into a sheet electrode, or may be compression-formed into a pellet electrode. Hereinafter, the case where the slurry is successively applied to the positive electrode current collector and then dried will be described.

[0085] [2-2-2-1. Active material content] The content of the positive electrode active material in the positive electrode active material layer is usually 80% by mass or more and 99.5% by mass or less.

[0086] [2-2-2-2.Conductive materials] Any known conductive material can be used as the conductive material. Specific examples include metal materials such as copper and nickel; graphite such as natural graphite and artificial graphite; carbon black such as acetylene black; and carbon-based materials such as amorphous carbon such as needle coke. The conductive material may be used alone or in any combination and ratio of two or more. The conductive material is used so that it is usually contained in the positive electrode active material layer in an amount of 0.01% by mass or more and 50% by mass or less.

[0087] [2-2-2-3. Binder] The binder used in producing the positive electrode active material layer is not particularly limited as long as it is a material that is dissolved or dispersed in a liquid medium for a slurry, for example, when the positive electrode active material layer is formed by a coating method. In view of weather resistance, chemical resistance, heat resistance, flame retardancy, and the like, preferred are fluorine-based resins such as polyvinyl fluoride, polyvinylidene fluoride, and polytetrafluoroethylene; and CN group-containing polymers such as polyacrylonitrile and polyvinylidene cyanide. In addition, mixtures, modified products, derivatives, random copolymers, alternating copolymers, graft copolymers, block copolymers, etc. of the above polymers can also be used. The binder may be used alone or in any combination and ratio of two or more kinds. Furthermore, when a resin is used as a binder, the weight average molecular weight of the resin is optional as long as it does not significantly impair the effects of the present invention, but is preferably 10,000 to 3,000,000. Here, the weight average molecular weight is usually 10,000 or more, preferably 50,000 or more, and particularly preferably 100,000 or more, and is usually 3,000,000 or less, preferably 950,000 or less, and particularly preferably 900,000 or less. When the molecular weight is within this range, the strength of the electrode is improved, and the electrode can be suitably formed. The proportion of the binder in the positive electrode active material layer is usually 0.1% by mass or more and 80% by mass or less.

[0088] [2-2-2-4. Current collector] The material of the positive electrode current collector is not particularly limited, and any known material can be used. Specific examples include metal materials such as aluminum, stainless steel, nickel plating, titanium, and tantalum. Among them, aluminum is preferable. The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, metal thin film, expanded metal, punched metal, foamed metal, etc. Among these, metal foil or metal thin film is preferable. The metal thin film may be appropriately formed into a mesh shape. When the positive electrode current collector has a plate or film shape, the current collector may have any thickness, but it is usually 1 μm or more and 1 mm or less.

[0089] [2-2-2-5. Thickness of positive electrode plate] The thickness of the positive electrode plate is not particularly limited, but from the viewpoint of high capacity and high output, the thickness of the positive electrode active material layer obtained by subtracting the thickness of the current collector from the thickness of the positive electrode plate is usually 10 μm or more and 500 μm or less on one side of the current collector.

[0090] [2-2-2-6. Electrode density] The positive electrode active material layer obtained by coating and drying is preferably compressed by a hand press, a roller press, or the like in order to increase the packing density of the positive electrode active material. The density of the positive electrode active material layer present on the current collector is usually 1.5 g / cm 3 More than 4.5g / cm 3 The following is the result.

[0091] [2-2-2-7. Surface coating of positive electrode plate] In addition, the positive electrode plate may have a substance having a different composition from that of the positive electrode plate attached to its surface, and the substance in question may be the same substance as the surface-attached substance that may be attached to the surface of the positive electrode active material.

[0092] [2-3. Negative electrode] The negative electrode has a negative electrode active material on at least a portion of the surface of a current collector.

[0093] [2-3-1. Negative electrode active material] The negative electrode active material used in the negative electrode is not particularly limited as long as it can electrochemically absorb and release metal ions. Specific examples include carbon-based materials, materials containing metal elements and / or metalloid elements that can be alloyed with Li, lithium-containing metal composite oxide materials, and mixtures thereof. Among these, it is preferable to use carbon-based materials, materials containing metal elements and / or metalloid elements that can be alloyed with Li, and mixtures of materials containing metal elements and / or metalloid elements that can be alloyed with Li and carbon-based materials, in terms of good cycle characteristics and safety, and excellent continuous charging characteristics. These may be used alone or in any combination of two or more.

[0094] [2-3-1-1. Carbon-based materials] Examples of carbonaceous materials include natural graphite, artificial graphite, amorphous carbon, carbon-coated graphite, graphite-coated graphite, and resin-coated graphite. Of these, natural graphite is preferred. The carbonaceous materials may be used alone or in any combination and ratio of two or more. Examples of natural graphite include scaly graphite, scaly graphite, and / or graphite particles obtained by subjecting such graphite to treatment such as spheroidization or densification. Among these, from the viewpoint of particle packing property or charge / discharge rate characteristics, spherical or ellipsoidal graphite particles that have been subjected to spheroidization treatment are particularly preferred. The average particle size (d50) of the graphite particles is usually 1 μm or more and 100 μm or less.

[0095] [2-3-1-2. Properties of carbon-based materials] The carbonaceous material as the negative electrode active material preferably satisfies at least one of the characteristics such as the physical properties and shape shown in the following (1) to (4), and particularly preferably satisfies several of them at the same time. (1) X-ray diffraction parameters The d value (interlayer distance) of the lattice plane (002 plane) of carbon-based materials determined by X-ray diffraction using the Gakushin method is usually 0.335 nm to 0.360 nm. Also, the crystallite size (Lc) of carbon-based materials determined by X-ray diffraction using the Gakushin method is usually 1.0 nm or more. (2) Volume-based average particle size The volume-based average particle size of a carbon-based material is the volume-based average particle size (median diameter d50) determined by a laser diffraction / scattering method, and is usually 1 μm or more and 100 μm or less. (3) Raman R value, Raman half-width The Raman R value of a carbon-based material is a value measured using argon ion laser Raman spectroscopy, and is usually 0.01 or more and 1.5 or less. In addition, the 1580 cm -1 The Raman half-width in the vicinity is not particularly limited, but is usually 10 cm -1 More than 100cm -1 The following is the result. (4) BET specific surface area The BET specific surface area of ​​a carbon-based material is the value of the specific surface area measured using the BET method, and is usually 0.1 m 2 ·g -1 More than 100m 2 ·g -1 The following is the result.

[0096] The negative electrode active material may contain two or more types of carbon-based materials having different properties. Here, the properties mean X-ray diffraction parameters, volume-based average particle size, Raman R value, Raman half-width, and BET specific surface area. Preferable examples include the case where the volume-based particle size distribution is not symmetric when centered on the median diameter, the case of containing two or more types of carbon-based materials having different Raman R values, and the case of containing two or more types of carbon-based materials having different X-ray parameters.

[0097] [2-3-1-3. Material containing a metal element and / or a metalloid element that can be alloyed with Li] Any conventionally known material containing a metal element and / or a metalloid element that can be alloyed with Li can be used. However, from the viewpoints of capacity and cycle life, for example, it is preferable that it is a single substance or a compound of a metal and / or a metalloid element, which may be coated with carbon, selected from the group consisting of Sb, Si, Sn, Al, As, and Zn. Further, when the material containing a metal element and / or a metalloid element that can be alloyed with Li contains two or more types of elements, the material may be an alloy material composed of an alloy of these metals. In addition, examples of the material containing a metal element and / or a metalloid element that can be alloyed with Li include oxides, nitrides, carbides, etc. These may contain two or more types of metal elements and / or metalloid elements that can be alloyed with Li. Among them, metallic Si (hereinafter, may be referred to as Si in some cases) or a Si-containing inorganic compound is preferable in terms of increasing the capacity. In addition, the material containing a metal element and / or a metalloid element that can be alloyed with Li may already be alloyed with Li during the production of the negative electrode described later.

[0098] In this specification, Si or a Si-containing inorganic compound is collectively referred to as a Si compound. Specific examples of the Si compound include SiO x (0≦x≦2), etc. Specific examples of the metal compound alloyed with Li include Li y Si(0<y≦4.4), Li2SiO 2+z (0<z≦2), etc. As the Si compound, silicon oxide (SiO x1 , 0 < x1 ≤ 2) is preferable in that its theoretical capacity is larger than that of graphite, or amorphous Si or nano-sized Si crystals are preferable in that alkali ions such as lithium ions can easily enter and exit, and high capacity can be obtained. When the material containing a metal element and / or a metalloid element that can alloy with Li is in the form of particles, its average particle diameter (d50) is usually 0.01 μm or more and 10 μm or less from the viewpoint of cycle life.

[0099] [2-3-1-4. Mixture of particles of a material containing a metal element and / or a metalloid element that can alloy with Li and graphite particles] The mixture of particles of a material containing a metal element and / or a metalloid element that can alloy with Li and graphite particles used as the negative electrode active material may be a mixture in which the particles of the material containing a metal element and / or a metalloid element that can alloy with Li and the aforementioned graphite particles are mixed in a state of particles of independent materials, or a composite in which the particles of the material containing a metal element and / or a metalloid element that can alloy with Li are present on the surface or inside of the graphite particles. The content ratio of the particles of the material containing a metal element and / or a metalloid element that can alloy with Li to the total of the particles of the material containing a metal element and / or a metalloid element that can alloy with Li and graphite particles is usually 1% by mass or more and 99% by mass or less.

[0100] [2-3-1-5. Lithium-containing metal composite oxide material] The lithium-containing metal composite oxide material used as the negative electrode active material is not particularly limited as long as it can occlude and release lithium ions, but a lithium-containing metal composite oxide material containing titanium is preferable from the viewpoint of high current density charge-discharge characteristics, and a composite oxide of lithium and titanium (hereinafter, may be abbreviated as "lithium titanium composite oxide") is more preferable, and a lithium titanium composite oxide having a spinel structure is particularly preferable because it greatly reduces the output resistance. Furthermore, the lithium and / or titanium of the lithium titanium composite oxide may be substituted with other metal elements, for example, at least one element selected from the group consisting of Al, Ga, Cu and Zn. Lithium titanium composite oxide, Li 4 / 3 Ti 5 / 3 O4, Li1Ti2O4 and Li 4 / 5 Ti 11 / 5 O4 is preferred. In addition, examples of lithium titanium composite oxides in which part of lithium and / or titanium is replaced with other elements include Li 4 / 3 Ti 4 / 3 Al 1 / 3 O4 is preferred.

[0101] [2-3-2. Negative electrode composition and manufacturing method] The negative electrode may be produced by any known method as long as it does not significantly impair the effects of the present invention. For example, the negative electrode may be produced by adding a binder, a liquid medium such as an aqueous solvent or an organic solvent, and if necessary, a thickener, a conductive material, a filler, etc. to the negative electrode active material to form a slurry, which is applied to a current collector, dried, and then pressed to form a negative electrode active material layer.

[0102] [2-3-2-1. Active material content] The content of the negative electrode active material in the negative electrode active material layer is usually 80% by mass or more and 99.5% by mass or less.

[0103] [2-3-2-2. Electrode density] The negative electrode active material layer obtained by coating and drying is preferably compressed by a hand press, a roller press or the like in order to increase the packing density of the negative electrode active material. There are no particular restrictions on the structure of the electrode when the negative electrode active material is made into an electrode, but the density of the negative electrode active material layer on the current collector is usually 1 g cm -3 More than 2.2g cm -3 The following is the result.

[0104] [2-3-2-3. Thickener] The thickener is usually used to adjust the viscosity of the slurry. The thickener is not particularly limited, but specifically includes carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, etc. These may be used alone or in any combination and ratio of two or more. When a thickener is used, the ratio of the thickener to the negative electrode active material is usually 0.1 mass % or more and 5 mass % or less.

[0105] [2-3-2-4. Binder] There are no particular limitations on the binder that binds the negative electrode active material, so long as it is a material that is stable in the nonaqueous electrolyte solution and the liquid medium used in the production of the electrode. Specific examples include rubber-like polymers such as SBR (styrene-butadiene rubber), isoprene rubber, butadiene rubber, fluororubber, NBR (acrylonitrile-butadiene rubber), and ethylene-propylene rubber; fluorine-based polymers such as polyvinylidene fluoride, polytetrafluoroethylene, and tetrafluoroethylene-ethylene copolymers. These may be used alone or in any combination and ratio of two or more.

[0106] The ratio of the binder to the negative electrode active material is usually 0.1% by mass or more and 20% by mass or less. In particular, when the binder contains a rubber-like polymer such as SBR as a main component, the ratio of the binder to the negative electrode active material is preferably 0.1% by mass or more and 5% by mass or less. Also, when the binder contains a fluorine-based polymer such as polyvinylidene fluoride as a main component, the ratio of the binder to the negative electrode active material is preferably 1% by mass or more and 15% by mass or less.

[0107] [2-3-2-5. Current collector] Any known current collector can be used to hold the negative electrode active material. Examples of the current collector for the negative electrode include metal materials such as aluminum, copper, nickel, stainless steel, and nickel-plated steel, and copper is particularly preferred from the standpoints of ease of processing and cost. The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, metal thin film, expanded metal, punched metal, foamed metal, etc. Among these, metal foil or metal thin film is preferable. The metal foil and metal thin film may be appropriately formed into a mesh shape. When the negative electrode current collector has a plate or film shape, the current collector may have any thickness, but it is usually 1 μm or more and 1 mm or less.

[0108] [2-3-2-6. Thickness of negative electrode plate] The thickness of the negative electrode (also called "negative electrode plate") is designed to match the positive electrode used and is not particularly limited, but the thickness of the negative electrode active material layer, calculated by subtracting the thickness of the current collector from the thickness of the negative electrode material, is usually 15 μm or more and 300 μm or less.

[0109] [2-3-2-7. Surface coating of negative electrode plate] The negative electrode plate may have a surface to which a substance having a different composition from the negative electrode active material (surface-attached substance) is attached. Examples of the surface-attached substance include oxides such as aluminum oxide, sulfates such as lithium sulfate, and carbonates such as lithium carbonate.

[0110] [2-4. Separator] A separator is usually interposed between the positive electrode and the negative electrode to prevent short circuiting. In this case, the non-aqueous electrolyte is usually impregnated into the separator before use. There are no particular limitations on the material and shape of the separator, and any known material can be used as long as it does not significantly impair the effects of the present invention.

[0111] [2-5.Battery design] [2-5-1. Electrode group] The electrode group may be either a laminated structure of the positive electrode plate and the negative electrode plate with the separator interposed therebetween, or a structure of the positive electrode plate and the negative electrode plate wound in a spiral shape with the separator interposed therebetween. The ratio of the volume of the electrode group to the internal volume of the battery is usually 40% or more and 90% or less.

[0112] [2-5-2. Current collection structure] In the case where the electrode group has the above-mentioned laminated structure, a structure in which the metal core parts of the electrode layers are bundled and welded to a terminal is preferably used. A structure in which multiple terminals are provided in the electrode to reduce resistance is also preferably used. In the case where the electrode group has the above-mentioned wound structure, the internal resistance can be reduced by providing multiple lead structures on each of the positive electrode and the negative electrode and bundling them to a terminal.

[0113] [2-5-3.Protection elements] The protective element may be a PTC (Positive Temperature Coefficient) element whose resistance increases with heat generation due to excessive current, a thermal fuse, a thermistor, a valve (current cutoff valve) that cuts off the current flowing through the circuit due to a sudden increase in the battery's internal pressure or temperature during abnormal heat generation, etc. It is preferable to select the above protective element so that it will not operate under normal use at high current, and it is even more preferable to design it so that abnormal heat generation or thermal runaway does not occur even without the protective element.

[0114] [2-5-4. Exterior body] A non-aqueous electrolyte secondary battery is usually constructed by housing the above-mentioned non-aqueous electrolyte, negative electrode, positive electrode, separator, etc. in an exterior body (exterior case). There are no limitations on this exterior body, and any known exterior body can be used as long as it does not significantly impair the effects of the present invention. The material of the exterior case is not particularly limited as long as it is a substance that is stable to the non-aqueous electrolyte solution used, but from the viewpoint of weight reduction, metal such as aluminum or an aluminum alloy, or a laminate film is preferably used. Examples of exterior cases using the above metals include those in which the metals are welded together by laser welding, resistance welding, or ultrasonic welding to form a sealed, airtight structure, and those in which the above metals are used with a resin gasket in between to form a crimped structure.

[0115] [2-5-5. Shape] The shape of the exterior case is also arbitrary, and may be, for example, cylindrical, rectangular, laminated, coin-shaped, large, or the like. EXAMPLES

[0116] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.

[0117] <Examples 1 to 2, Comparative Examples 1 to 3> [Preparation of non-aqueous electrolyte] In a dry argon atmosphere, LiPF6 that had been thoroughly dried was dissolved as an electrolyte at 1.0 mol / L (12.4 mass%; as the concentration in the non-aqueous electrolyte) in a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (volume ratio EC:EMC=3:7). A reference non-aqueous electrolyte was prepared by adding 1 part by mass of vinylene carbonate to 100 parts by mass of this electrolyte. A non-aqueous electrolyte was prepared by adding a compound represented by general formula (I) as additive 1 and a sulfur trioxide complex as additive 2 in the amounts shown in Table 1 below. In Table 1, "-" means that additive 1 and additive 2 were not added.

[0118] [Preparation of negative electrode] 98 parts by mass of natural graphite was mixed with 1 part by mass of an aqueous dispersion of sodium carboxymethylcellulose (concentration of sodium carboxymethylcellulose: 1% by mass) and 1 part by mass of an aqueous dispersion of styrene-butadiene rubber (concentration of styrene-butadiene rubber: 50% by mass) as a thickener and binder, and the mixture was mixed in a disperser to form a slurry. The obtained slurry was applied to one side of a copper foil having a thickness of 10 μm, dried, and pressed to form a negative electrode.

[0119] [Half-cell fabrication] The negative electrode, a sufficient amount of metallic lithium foil as a counter electrode, the nonaqueous electrolyte, and a polyethylene separator were stacked in this order, and the battery element thus obtained was placed in a 2032 coin battery can and crimped with a crimping machine to prepare a coin-type half cell.

[0120] [Run-in] The obtained half cell was charged at 25°C to 5 mV at a constant current equivalent to 0.05 C, then charged at a constant voltage of 5 mV until the current value reached 0.01 C, and discharged at a constant current of 0.05 C to 1500 mV. Next, at the same temperature, it was charged at a current equivalent to 0.1 C to 5 mV, then charged until the current value at a constant voltage of 5 mV reached 0.05 C, and discharged at a current value of 0.1 C to 1500 mV. This was repeated for two cycles to stabilize the half cell and complete the break-in.

[0121] [Evaluation of capacity retention rate during repeated charging and discharging] After the break-in, the half-cell was charged to 5 mV at a constant current equivalent to 0.5 C, then charged at a constant voltage of 5 mV until the current value reached 0.1 C, and discharged to 1500 mV at a constant current of 0.5 C. The discharge capacity at this time was recorded as the first cycle discharge capacity. After that, charging to 5 mV and discharging to 1500 mV were repeated 51 times. The capacity retention rate (%) during repeated charging and discharging was calculated from (discharge capacity at the 52nd cycle)÷(discharge capacity at the 1st cycle)×100, and the capacity retention rate ratio normalized by setting the capacity retention rate of Comparative Example 1 at 100 is shown in Table 1 below.

[0122] [Table 1]

[0123] From Table 1, it can be seen that in Examples 1 and 2, which used a non-aqueous electrolyte solution containing both the compound represented by general formula (I) and a sulfur trioxide complex, the capacity retention ratio was improved.

Claims

1. A non-aqueous electrolyte solution in which an electrolyte salt is dissolved in a non-aqueous solvent, A non-aqueous electrolyte solution comprising a compound represented by the following general formula (I) and a sulfur trioxide complex: 【Chemistry 1】 (In the formula, M + indicates an alkali metal cation.)

2. The non-aqueous electrolyte solution according to claim 1, characterized in that the molar ratio of the compound represented by the general formula (I) to the sulfur trioxide complex in the non-aqueous electrolyte solution is 95:5 to 40:

60.

3. The non-aqueous electrolyte solution according to claim 1, characterized in that the molar ratio of the compound represented by the general formula (I) to the sulfur trioxide complex in the non-aqueous electrolyte solution is 85:15 to 60:

40.

4. The sulfur trioxide complex is, for example, a pyridine-sulfur trioxide complex, a trimethylamine-sulfur trioxide complex, a triethylamine-sulfur trioxide complex, an N,N-dimethylacetamide-sulfur trioxide complex, an N,N-dimethylformamide-sulfur trioxide complex, an N-methyl-2-pyrrolidone-sulfur trioxide complex, a dimethylsulfone-sulfur trioxide complex, or a thietane. The non-aqueous electrolyte solution according to claim 1, which is at least one selected from the group consisting of 1,1-dioxide-sulfur trioxide complex, 3-sulfolene-sulfur trioxide complex, sulfolane-sulfur trioxide complex, dimethyl sulfide-sulfur trioxide complex, dimethyl sulfoxide-sulfur trioxide complex, 1,4-dioxane-sulfur trioxide complex, 1,3-dioxane-sulfur trioxide complex, trimethyl phosphate-sulfur trioxide complex, triethyl phosphate-sulfur trioxide complex, tri-n-butyl phosphate-sulfur trioxide complex, triphenyl phosphate-sulfur trioxide complex, tri-p-cresyl phosphate-sulfur trioxide complex, tri-tert-butyl phosphate, trimethyl phosphite-sulfur trioxide complex, triethyl phosphite-sulfur trioxide complex, tri-n-butyl phosphite-sulfur trioxide complex, triphenyl phosphite-sulfur trioxide complex, tri-p-cresyl phosphite-sulfur trioxide complex, and tri-tert-butyl phosphite.

5. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte in which an electrolyte salt is dissolved in a non-aqueous solvent, A non-aqueous electrolyte secondary battery, wherein the non-aqueous electrolyte is the non-aqueous electrolyte according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Pyridine sulfur trioxide complexes as electrolyte components for high voltage batteries.

    JP2020504434A